CLINICAL CHARACTERISTICS AND PROGNOSTIC FACTORS AFFECTING CLINICAL OUTCOMES IN CYTOMEGALOVIRUS RETINITIS WITH OR WITHOUT HIV INFECTION. Issue 1 (January 2023) - Su, Yu-Ting; Chen, Yi-JUN; Lin, Chang-Ping; Hsieh, Yi-Ting; Yang, Chung-May; Chiu-Ang, Angelique; Yeh, Po-Ting
Abstract : Cytomegalovirus retinitis mainly affects HIV cases, but non-HIV cases are increasing and they have different clinical features and outcomes. A combination antiretroviral therapy improved survival and decreased cytomegalovirus retinitis recurrence in HIV cases. Poor initial visual acuity, RD, and higher plasma cytomegalovirus titers are risk factors of poor visual acuity outcomes in both groups. Abstract : Purpose: To explore the clinical features and outcomes of cytomegalovirus retinitis (CMVR) in patients with HIV and non-HIV. Methods: This retrospective cohort study included all patients with CMVR in National Taiwan University Hospital from 2013 to 2018. Demographic data, clinical characteristics, CMVR recurrence, and overall survival were compared between the HIV and non-HIV groups. Generalized estimating equation models were implemented to analyze the risk factors of poor visual prognosis. The Kaplan–Meier survival analysis was performed to investigate recurrence and survival. Results: A total of 66 patients (95 eyes) with CMVR were enrolled, with no significant differences between the HIV (41 patients; 61 eyes) and non-HIV (25 patients; 34 eyes) groups in initial/final visual acuity, lesion area, or viral loads. Poor visual outcome was associated with poor initial visual acuity, retinal detachment, and a higher plasma cytomegalovirus titer. The HIV group had significantly longer survival rate ( P = 0.033) and lower recurrence rate ( P = 0.01) than the non-HIV group, and it also presented with better prognosis in recurrence-free survival analysis ( P = 0.01). Conclusion: Patients with CMVR without HIV had higher mortality and recurrence rates than the HIV group. Risk factors of poor visual outcome included poor initial visual acuity, retinal detachment, and a high plasma cytomegalovirus titer.